2018
DOI: 10.1111/ijfs.13888
|View full text |Cite
|
Sign up to set email alerts
|

Production of trans‐free margarine fat by enzymatic interesterification of soy bean oil, palm stearin and coconut stearin blend

Abstract: Trans‐free structure lipids (SLs) were prepared from enzymatic interesterification (EI) of soybean oil (SBO), palm stearin (PS) and coconut stearin (CNS) blends in different ratios (0:70:30, 10:60:30, 20:50:30, 30:40:30 and 40:30:30% wt.) using Lipozyme RM IM at 65 °C for 8 h. After EI, the fatty acid composition of the SLs exhibited no change from the physical blends (PBs). Medium‐chain fatty acid was incorporated into the triacylglycerol of the SLs. The melting completion temperature decreased from 50–54 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…For example, trans-fee plastic fats are mainly used as shortening and margarine fats to replace traditionally used hydrogenated oils and animal fats. Extensive studies have been conducted to exploit novel trans-free fats and assess their potential performance in various food products such as margarines (Hu, Xu, & Yu, 2017;Lakum & Sonwai, 2018;Li et al, 2018b;Ornla-Ied, Sonwai, & Lertthirasuntorn, 2016;Pande, Akoh, & Shewfelt, 2012), shortenings (Saghafi et al, 2018;Xu et al, 2018), as well as fat-frozen special fats (Zhu et al, 2019;Zhu et al, 2018b;Zhu et al, 2017). CBEs, as the name indicates, have been primarily applied to partially substitute cocoa butter in chocolate products, such as dark chocolates (De Clercq et al, 2017;Jin, Jin, Wang, & Akoh, 2019;Souza & Block, 2018), white chocolates (Bahari & Akoh, 2018b), and milk chocolates (Ackar et al, 2015).…”
Section: Potential Food Applications Of Slsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, trans-fee plastic fats are mainly used as shortening and margarine fats to replace traditionally used hydrogenated oils and animal fats. Extensive studies have been conducted to exploit novel trans-free fats and assess their potential performance in various food products such as margarines (Hu, Xu, & Yu, 2017;Lakum & Sonwai, 2018;Li et al, 2018b;Ornla-Ied, Sonwai, & Lertthirasuntorn, 2016;Pande, Akoh, & Shewfelt, 2012), shortenings (Saghafi et al, 2018;Xu et al, 2018), as well as fat-frozen special fats (Zhu et al, 2019;Zhu et al, 2018b;Zhu et al, 2017). CBEs, as the name indicates, have been primarily applied to partially substitute cocoa butter in chocolate products, such as dark chocolates (De Clercq et al, 2017;Jin, Jin, Wang, & Akoh, 2019;Souza & Block, 2018), white chocolates (Bahari & Akoh, 2018b), and milk chocolates (Ackar et al, 2015).…”
Section: Potential Food Applications Of Slsmentioning
confidence: 99%
“…For example, MLCTs can be used to provide readily available energy by introducing medium‐chain fatty acids (for example, caprylic acid (C8:0) and capric acid (C10:0); Abed et al., ; He, Li, Guo, & Chen, ). Trans ‐free plastic fats are synthesized mainly for replacing partially hydrogenated vegetable oils such as margarine and shortening fats (Lakum & Sonwai, ; Li et al., ). HMFSs can be obtained with palmitic acids primarily at the sn ‐2 position and unsaturated FAs (for example, oleic acids) mainly at the sn ‐1,3 positions to mimic human milk fat, which is the “gold standard” (Şahin‐Yeşilçubuk & Akoh, ; Zou, Pande, & Akoh, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study showed that the application of soft fraction of palm oil can deliver a higher volume in baked cakes [6]. Generally, a highly functional specialty fat is achievable by blending, hydrogenation, and interesterification process [7].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of fats and oils is an important and useful technique to improve their physicochemical and thermal properties. This technique including blending, hydrogenation, fractionation, and chemical and enzymatic interesterification are used to produce fats for margarine, confectionery, cosmetic, and chemical industries (Timms, 2005;Gibon, 2006;Momeny et al, 2013;Kang et al, 2013;Jin et al, 2016;Kadivar et al, 2016;Lakum and Sonwai, 2018). Solvent fractionation is applied to produce structural lipids such as hard fats (high-melting-point triacylglycerols), polyunsaturated fatty acid-rich oil, creams, and margarines due to the high separation efficiency and yield of aimed fractions with sharper melting properties (Gibon, 2006;Kellens et al, 2007;Mu et al, 2016;Jin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, palm oil is fractionated into palm stearin and liquid and is the most widely fractionated oil worldwide (Senanayake and Shahidi, 2005;Gibon, 2006). Meanwhile, these palm oil fractions have been used to prepare wide variety of food products, especially confectionery products (Jahurul, Zaidul, Norulaini, Sahena, Kamaruzzaman et al, 2014;Jahurul, Zaidul, Norulaini, Sahena, Abedin et al, 2014;Lakum and Sonwai, 2018).…”
Section: Introductionmentioning
confidence: 99%